Theta burst stimulation improves overt visual search in spatial neglect independently of attentional load. (December 2015) - Cazzoli, Dario; Rosenthal, Clive R.; Kennard, Christopher; Zito, Giuseppe A.; Hopfner, Simone; Müri, René M.; Nyffeler, Thomas
Abstract: Visual neglect is considerably exacerbated by increases in visual attentional load. These detrimental effects of attentional load are hypothesised to be dependent on an interplay between dysfunctional inter-hemispheric inhibitory dynamics and load-related modulation of activity in cortical areas such as the posterior parietal cortex (PPC). Continuous Theta Burst Stimulation (cTBS) over the contralesional PPC reduces neglect severity. It is unknown, however, whether such positive effects also operate in the presence of the detrimental effects of heightened attentional load. Here, we examined the effects of cTBS on neglect severity in overt visual search (i.e., with eye movements), as a function of high and low visual attentional load conditions. Performance was assessed on the basis of target detection rates and eye movements, in a computerised visual search task and in two paper-pencil tasks. cTBS significantly ameliorated target detection performance, independently of attentional load. These ameliorative effects were significantly larger in the high than the low load condition, thereby equating target detection across both conditions. Eye movement analyses revealed that the improvements were mediated by a redeployment of visual fixations to the contralesional visual field. These findings represent a substantive advance, because cTBS led to an unprecedented amelioration of overt search efficiency that was independent of visual attentional load.